Review of current and emerging therapies in acute ischemic stroke. (20th July 2009) - Novakovic, R; Toth, G; Purdy, P D
Abstract : The statistics for stroke in the USA reads like a familiar ad slogan cited in most papers pertaining to acute ischemic stroke (AIS). Stroke is the third leading cause of death in the USA. While stroke ranks third among all causes of death, behind diseases of the heart and cancer, it is the leading cause of serious long-term disability in the USA. 1 Approximately 795 000 people, 87% of whom are ischemic, suffer from stroke each year in the USA. 2 That means that on average, every 40 seconds someone within the USA develops a stroke. For 2009 the combined direct and indirect cost of stroke, from hospitalization and rehabilitation to institutionalization, is estimated at $68.9 billion within the USA. 2